Orbital IgG4-Related Disease Detected by 11C-Methionine PET/CT. (October 2015) - Yamane, Tomohiko; Seto, Akira; Suzuki, Tomonari; Yokota, Kazuhiro; Li, Chih-Ping; Mimura, Toshihide; Kuji, Ichiei
<x xml:space="preserve">Abstract</x> Abstract A 64-year-old man presented with a complaint of left exophthalmos. Whole-body 18F-FDG PET/CT showed increased uptake in the soft tissue masses in the orbits, peripancreas, and left renal hilum. 11C-methionine (MET) PET/CT of the head and neck showed increased uptake in the orbits, and the SUVmax of the left orbital lesion was 7.0. The patient was finally diagnosed as IgG4-related disease by the results of increased serum IgG4 and the biopsy of the orbital lesion. Although 11C-MET is generally considered as a tumor-specific tracer, fibrous tissues of IgG4-related disease may be visualized by 11C-MET PET/CT.